A novel gain-of-function STAT1 mutation resulting in basal phosphorylation of STAT1 and increased distal IFN-γ-mediated responses in chronic mucocutaneous candidiasis. Issue 2 (December 2015) - Martinez-Martinez, Laura; Martinez-Saavedra, Maria Teresa; Fuentes-Prior, Pablo; Barnadas, Maria; Rubiales, Maria Victoria; Noda, Judith; Badell, Isabel; Rodríguez-Gallego, Carlos; Calle-Martin, Oscar de la
Highlights: A new GOF STAT1 mutation (K298N) is responsible for chronic mucocutaneous candidiasis. K298N results in hyperphosphorylation of STAT1, with and without IFN-γ stimulation. K298N induces increased IFN-γ-mediated responses, even in the absence of stimuli. Patients present low levels of IL-17 + T cells, and most of them also produce IFN-γ. The patients presented an altered cytokine profile after polyclonal stimulation. Abstract: Gain-of-function STAT1 mutations have recently been associated with autosomal dominant chronic mucocutaneous candidiasis (CMC). The purpose of this study was to characterize the three members of a non-consanguineous family, the father and his two sons, who presented with recurrent oral thrush and ocular candidiasis since early childhood. The three patients had reduced levels of IL-17-producing T cells. This reduction affected specifically IL-17 + IFN-γ − T cells, because the levels of IL-17 + IFN-γ + T cells were similar to controls. We found that PBMC (peripheral blood mononuclear cells) from the patients did not respond to Candida albicans ex vivo . Moreover, after polyclonal activation, patients' PBMC produced lower levels of IL-17 and IL-6 and higher levels of IL-4 than healthy controls. Genetic analyses showed that the three patients were heterozygous for a new mutation in STAT1 (c.894A > C, p.K298N) that affects a highly conserved residue of the coiled-coil domain of STAT1. STAT1 phosphorylation levels were significantly higher in patients' cells than in healthy controls, both in basal conditions and after IFN-γ stimulation, suggesting a permanent activation of STAT1. Cells from the patients also presented increased IFN-γ-mediated responses measured as MIG and IP-10 production. In conclusion, we report a novel gain-of-function mutation in the coiled-coil domain of STAT1, which increases STAT1 phosphorylation and impairs IL-17-mediated immunity. The mutation is responsible for CMC in this family with autosomal dominant inheritance of the disease.